MiR-1208 Increases the Sensitivity to Cisplatin by Targeting TBCK in Renal Cancer Cells - Kim, Eun-Ae (Int J Mol Sci, 2019)
MicroRNAs (miRNAs) can be used to target a variety of human malignancies by targeting their oncogenes or tumor suppressor genes. Recent evidence has shown that miRNA-1208 (miR-1208) was rarely expressed in a variety of cancer cells, suggesting the possibility that miR-1208 functions as a tumor suppressor gene. Herein, ectopic expression of miR-1208 induced the accumulation of sub-G1 populations and the cleavage of procaspase-3 and PARP, which could be prevented by pre-treatment with the pan-caspase inhibitor, Z-VAD. In addition, miR-1208 increased the susceptibility to cisplatin and TRAIL in Caki-1 cells. Luciferase reporter assay results showed that miR-1208 negatively regulates TBC1 domain containing kinase (TBCK) expression by binding to the miR-1208 binding sites in the 3′-untranslated region of TBCK. In addition, miR-1208 specifically repressed TBCK expression at the transcriptional level. In contrast, inhibition of endogenous miR-1208 by anti-miRs resulted in an increase in TBCK expression. Downregulation of TBCK induced by TBCK-specific siRNAs increased susceptibility to cisplatin and TRAIL. These findings suggest that miR-1208 acts as a tumor suppressor and targets TBCK directly, thus possessing great potential for use in renal cancer therapy.